Targeting atrial fibrillation in HFpEF: the emerging role of pulsed field ablation - Parwani, A. S.; Kossmann, B.; Schweiger, V. (Frontiers in Physiology, 2025)
With a rising prevalence of heart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF), their frequent coexistence poses a growing clinical challenge for clinicians worldwide. HFpEF and AF share common risk factors and pathophysiological mechanisms, contributing to worsening cardiac function and remodeling. Traditional pharmacological rhythm control strategies often proved ineffective in heart failure patients, prompting increased interest in catheter ablation. Pulse Field Ablation (PFA), a novel non-thermal ablation technique utilizes irreversible electroporation and offers promising safety and efficacy advantages over conventional thermal methods by selectively targeting myocardial cells while minimizing collateral tissue damage. Early clinical data suggest that PFA may result in less atrial fibrosis and preserves atrial compliance, which could be particularly beneficial in HFpEF where diastolic function is central. Although ablation outcomes in HFpEF have been less extensively studied than in heart failure with reduced ejection fraction (HFrEF), preliminary studies report low complication rates, improved hemodynamics, and ameliorated outcomes following ablation. Registry data and subanalyses of trials like EAST-AFNET4 support early rhythm control, while the ongoing CABA-HFpEF-DZHK27 trial aims to determine whether catheter ablation improves cardiovascular outcomes in this specific population. As PFA gains traction for its procedural efficiency and favorable safety profile, its role in managing AF in HFpEF may expand. However, further robust, randomized studies are necessary to define its long-term benefits and may establish PFA as a standard therapy in this complex patient cohort.